Assessing the performance of a physically-based soil moisture module integrated within the Soil and Water Assessment Tool. (November 2018) - Qi, Junyu; Zhang, Xuesong; McCarty, Gregory W.; Sadeghi, Ali M.; Cosh, Michael H.; Zeng, Xubin; Gao, Feng; Daughtry, Craig S.T.; Huang, Chengquan; Lang, Megan W.; Arnold, Jeffrey G.
Abstract: A Richards-equation-based soil moisture module was developed and integrated within the Soil and Water Assessment Tool (SWAT). Four years of daily soil moisture measurements from 10 monitoring stations at three depths (i.e., 5, 10, and 50 cm) in the Choptank River watershed, Maryland, were used to test the module performance. Results show that, as compared with the original SWAT soil moisture module, the Richards-equation-based soil moisture module improved R 2 from 0.12 to 0.45 and reduced soil moisture simulation bias (mean[simulation] – mean[measurement]) from −0.10 to −0.02 (m 3 m −3 ), averaged across the 10 stations at soil surface layer (i.e., 5 cm depth). Noticeable improvements were also observed for deeper soil layers, and for both dry and wet periods. Notably, the soil moisture coupling strength between different soil layers was substantially improved with the new module. The enhanced SWAT model is expected to better inform soil water and irrigation management. Highlights: We developed RSWAT that integrates the physically-based Richards equation into SWAT2012. In situ soil moisture data from 10 moisture stations and at three depths were compiled to evaluate RSWAT performance. RSWAT substantially improved surface soil moisture prediction compared with the original bucket soil water module within SWAT. RSWAT outperforms the original SWAT for both wet and dry periods. RSWAT better captures soil moisture coupling strength than the original SWAT.